Castellated Beams with Fiber-Reinforced Lightweight Concrete Deck Slab as a Modified Choice for Composite Steel-Concrete Beams Affected by Harmonic Load - Dakhel, Z. H.; Mohammed, S. D. (Engineering, Technology & Applied Science Research, 2022)
The behavior investigation of castellated beams with fiber-reinforced lightweight concrete deck slab as a modified choice for composite steel-concrete beams affected by harmonic load is presented in this study. The experimental program involved six fixed-supported castellated beams of 2140mm size. Three types of concrete were included: Normal Weight Concrete (NWC), Lightweight Aggregate Concrete (LWAC), and Lightweight Fiber-Reinforced Aggregate Concrete (LWACF). The specimens were divided into two groups: the first comprised three specimens tested under harmonic load effect of 30Hz operation frequency for 3 days, then the residual strength was determined through static load application. The second group included three specimens identical to those of group I, tested under static load only. The results show that LWAC was more influential than LWACF under harmonic load. The reduction in the residual strength of LWACF and NWC deck corresponding to the harmonic load was 0.94 and 0.7% respectively. The outcome proved that using LWACF as a deck for the castellated steel beams affected by harmonic load presents a significant choice with weight reduction of 16% compared to NWC. Steel fiber’s tensile strength 1700MPa enhanced the absorbed energy and the ductility factor by 0.4 and 0.5% respectively.